The Synthetic Peptide GA-Hecate and Its Analogs Inhibit Multiple Steps of the Chikungunya Virus Infection Cycle In Vitro - Ayusso, Gabriela Miranda [UNESP]; da Silva Sanches, Paulo Ricardo [UNESP]; Carvalho, Tamara [UNESP]; Santos, Igor Andrade; Martins, Daniel Oliveira Silva [UNESP]; Lima, Maria Letícia Duarte [UNESP]; da Conceição, Pâmela Jóyce Previdelli [UNESP]; Bittar, Cíntia [UNESP]; Merits, Andres; Cilli, Eduardo Maffud [UNESP]; Jardim, Ana Carolina Gomes [UNESP]; Rahal, Paula [UNESP]; et al. (MDPI, 2023)
Chikungunya virus (CHIKV) belongs to the Alphavirus genus and is responsible for significant outbreaks worldwide. Currently, there is no approved antiviral therapy against CHIKV. Bioactive peptides have great potential for new drug development. Here, we evaluated the antiviral activity of the synthetic peptide GA-Hecate and its analogs PSSct1905 and PSSct1910 against CHIKV infection. Initial screening showed that all three peptides inhibited the CHIKV replication cycle in baby hamster kidney fibroblast cells (BHK-21) and human hepatocarcinoma epithelial cells (Huh-7). GA-Hecate and its analog PSSct1905 were the most active, demonstrating suppression of viral infection by more than 91%. The analog PSSct1905 exhibited a protective effect in cells against CHIKV infection. We also observed that the analogs PSSct1905 and PSSct1910 affected CHIKV entry into both cell lines, inhibiting viral attachment and internalization. Finally, all tested compounds presented antiviral activity on the post-entry steps of CHIKV infection in all cells evaluated. In conclusion, this study highlights the potential of the peptide GA-Hecate and its analogs as novel anti-CHIKV compounds targeting different stages of the viral replication cycle, warranting the development of GA-Hecate-based compounds with broad antiviral activity.
Keywords: analogs; antiviral; chikungunya; peptides